Plan de mejoramiento Integral barrial en los asentamientos del barrio El Oasis de la comuna 6 en la ciudad de Neiva - Huila - Córdoba Arcila, Juan Sebastián (Universidad Antonio Nariño, 2024)
The realization of the present investigation is on the studies of the subnormal settlements, being its inhabitants a vulnerable population, mainly in the commune 6 of Neiva the subject of the subnormal settlements is approached in a direct and practical way by the protection zone El Loro where a considerable part of families of this commune reside today in this unofficial zone and face diverse urban and city-related problems that have repercussions on the growth of these people. For this reason, it is justified with relevant data the relevance of addressing this issue from an architectural perspective and its urban design strategies, such as the 4 criteria that highlight circularity, living, working and recreation as important pillars for development and offer a model of urban planning, generating proposals raised in this research.